2017
DOI: 10.1002/hbm.23624
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related mapping of intracortical myelin from late adolescence to middle adulthood using T1‐weighted MRI

Abstract: Magnetic resonance imaging (MRI) studies in humans have reported that the T -weighted signal in the cerebral cortex follows an inverted "U" trajectory over the lifespan. Here, we investigated the T -weighted signal trajectory from late adolescence to middle adulthood in humans to characterize the age range when mental illnesses tend to present, and efficacy of treatments are evaluated. We compared linear to quadratic predictors of age on signal in 67 healthy individuals, 17-45 years old. We investigated ¼, ½, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 70 publications
(98 reference statements)
5
42
0
Order By: Relevance
“…There was no significant change in VO 2 peak O 2 /kg within either group (passive control p = .17, exercise p = .6), nor with VT1 O 2 /kg (passive control p = .31, exercise p = .73), but there were increasing trends in the exercise group and a decrease in the passive control group in both measures. An average R 1 map for the control group is displayed in Figure , which resembles previously reported myelin maps (Dinse et al, ; Glasser & Van Essen, ; Marques, Khabipova, & Gruetter, ; Rowley et al, ; Shafee, Buckner, & Fischl, ).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…There was no significant change in VO 2 peak O 2 /kg within either group (passive control p = .17, exercise p = .6), nor with VT1 O 2 /kg (passive control p = .31, exercise p = .73), but there were increasing trends in the exercise group and a decrease in the passive control group in both measures. An average R 1 map for the control group is displayed in Figure , which resembles previously reported myelin maps (Dinse et al, ; Glasser & Van Essen, ; Marques, Khabipova, & Gruetter, ; Rowley et al, ; Shafee, Buckner, & Fischl, ).…”
Section: Resultssupporting
confidence: 80%
“…In this study, we probed cortical microstructure using quantitative R 1 (1/T 1 ), as T 1 values have previously been shown to be spatially correlated with intracortical myelin levels in the common marmoset (Bock, Kocharyan, Liu, & Silva, ). Quantitative R 1 imaging and its related qualitative parameter T 1 ‐weighted imaging (T 1 W) have been previously used to study cortical microstructure, often in reference to intracortical myelin, in humans (Dinse et al, ; Ferguson et al, ; Fracasso et al, ; Lutti, Dick, Sereno, & Weiskopf, ; Rowley et al, ; Sehmbi et al, ; Sereno, Lutti, Weiskopf, & Dick, ). A benefit of R 1 over T 1 W imaging is that it provides a quantitative value that at a given MRI field strength is independent of the method of measurement and similar across studies (Trampel, Bazin, Pine, & Weiskopf, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous MR studies have shown that myelination in humans begins in the subcortex (Partridge et al, 2004;Deoni et al, 2011;Barkovich et al, 1988;Nakagawa et al, 1998; for review, see Paus et al, 2001;Baumann & Pham-Dinh, 2001). Further, MR studies have found myelination of primary and association cortex progresses during childhood (Deoni et al, 2015;Dean et al, 2016) and adolescence (Grydeland et al, 2013), before age-related de-myelination begins during middle adulthood (Vidal-Piñeiro et al, 2016;Grydeland et al, 2013;Salat et al, 2009; see also Rowley et al, 2017). DTI investigations have also found that white matter structure within association cortex develops over extended periods, typically to beyond late adolescence (Klinberg et al, 1999;Barnea-Goraly, 2005).…”
Section: Development and Cortical Myelinationmentioning
confidence: 97%
“…Recently, there has been a growing interest in assessing the content of intra‐cortical myelin via noninvasive but indirect neuroimaging techniques. While other quantifications of intra‐cortical myelin are under development (Alonso‐Ortiz, Levesque, & Pike, ; Does, ; Heath, Hurley, Johansen‐Berg, & Sampaio‐Baptista, ), previous magnetic resonance imaging (MRI) studies have shown that the ratio between the T1‐ and T2‐weighted MRI signal intensity can provide useful information regarding the neocortical myelo‐architecture (Grydeland et al, ; Rowley et al, ; Shafee, Buckner, & Fischl, ). The T1‐weighted and T2‐weighted signals are the two basic MRI signals which, respectively, relate to the spin–lattice and spin–spin relaxation time (the spin is the intrinsic rotation of protons while the lattice is their surrounding environment).…”
Section: Introductionmentioning
confidence: 99%
“…The MRI T1‐/T2‐weighted ratio also consistently estimates the relative changes in intra‐cortical myelin across the lifespan, that is, from childhood throughout adolescence to adulthood and old age (Grydeland et al, ; Rowley et al, ; Shafee et al, ). Variability in the T1‐/T2‐weighted contrast ratio has also been linked to individual differences in cognitive performances (Grydeland et al, ).…”
Section: Introductionmentioning
confidence: 99%